Survey of individual readiness of the emergency department nurses in dealing with disasters - Shahba Nimezad; Alice Khachian; Tahereh Alsadat Khoubbin Khoshnazar; Fereydoon Khayeri (Shahrekord University of Medical Sciences, 2022)
Background and aims: Examining the preparedness of nurses, including the individual preparedness of emergency nurses, has yet to be investigated. Given the hypocrisy of emergency nurses as the first group of the treatment team in responding to accidents and disasters and reducing the amount of damage to patients, the present study aims to investigate the individual preparedness of emergency nurses of Iran University of Medical Sciences in facing disasters in 2019. Methods: The present study was descriptive-cross-sectional in which the preparedness of 190 nurses in the emergency departments of the teaching and therapeutic hospital affiliated with the Iran University of Medical Sciences was investigated. Data collection was done using a demographic characteristics checklist and the 37-item questionnaire on than individual preparedness of nurses in disasters. Data analysis was done by SPSS version 21 using descriptive statistics (frequency, percentage, mean±standard deviation) and to determine statistical significance, inferential statistics (independent t-test, analysis of variance, Spearman's correlation coefficient, Tukey's test) at a significance level (P value) of<0.05 was used. Results: The study's results showed that nurses' preparedness was at a reasonable level. The highest average score was obtained for the teamwork communication skills domain (86.35±14.01), and the lowest average score for the clinical skills in the disaster response phase domain (10.55±20.50) based on 0 to 100 was obtained (P<0.001). Among the demographic variables, age (31.84±5.81 years) and nursing experience in the emergency department (7.02±5.24) had a significant relationship with nurses' preparedness (P<0.001). Conclusion: Having experience in nursing work and working in the emergency department plays a role in increasing the level of individual preparedness of nurses in disasters. Therefore, the recruitment of experienced staff in the emergency department and their hiring to training less professional staff should be encouraged. Implementing educational programs in the form of theoretical training and the performance of practical programs can effectively improve the level of preparedness of nurses, especially novice and apprenticeship ones, in facing disasters.